Alternative Cropping Systems with Limited Irrigation - A. Schlegel; D. Bond (Kansas Agricultural Experiment Station Research Reports, 2021)
A limited irrigation study involving four cropping systems and evaluating four crop rotations was initiated at the Southwest Research-Extension Center near Tribune, KS, in 2012. The cropping systems were two annual systems (continuous corn and continuous grain sorghum) and two 2-year systems (corn-grain sorghum and corn-winter wheat). In 2020, corn yields were similar for all rotations, although averaged across the past 8 years, corn yields were greater following wheat than following corn. There were no significant differences in grain sorghum yields in 2020, which was similar to the multi-year average. Wheat yields were below the multi-year average.
Keywords: Corn; grain sorghum; winter wheat; deficit irrigation; irrigated crop rotations